El aprendizaje de la lectoescritura en estudiantes con discapacidad intelectual de séptimo año de educación general básica - Salvatierra Pastoriza, Gabriela Steffanie (2021)
The objective of this research is to analyze the literacy processes in students with mild intellectual disabilities in the 7th year of Basic General Education to improve their academic performance. In view of this need, a bibliographic study was carried out where the main definitions and characteristics of the methodological strategies that served to develop a set of activities for the proposal were evidenced. For this, the use of a quantitative approach with descriptive, documentary and field research was proposed, the latter comprises an intentional sample of 1 manager, 7 teachers, 15 students with mild intellectual disabilities and 15 parents. The instruments applied were the observation guide, the survey and the interview. ……